2016
DOI: 10.1159/000442892
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Subthalamic Nucleus Stimulation on Pedunculopontine Nucleus Neural Activity

Abstract: Background: The pedunculopontine nucleus has recently been proposed as an alternative target for deep brain stimulation for the treatment of medically intractable Parkinson's disease. The suggested indication for pedunculopontine nucleus deep brain stimulation is severe and medically intractable axial symptoms such as gait and postural impairment. Objective: Our goal in this study was to describe the effects of subthalamic nucleus stimulation on pedunculopontine nucleus electrophysiological activity. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Conventionally, the “straight lead pathway” method is used for lead implantation. Under most circumstances, multi-target simulation/recording can only be achieved via increased number of leads181920212223242731. In this case, the “curved lead pathway” method may complement the current “straight lead pathway” method, make lead implantation for multiple targets more convenient, and expand experimental techniques of brain function research.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Conventionally, the “straight lead pathway” method is used for lead implantation. Under most circumstances, multi-target simulation/recording can only be achieved via increased number of leads181920212223242731. In this case, the “curved lead pathway” method may complement the current “straight lead pathway” method, make lead implantation for multiple targets more convenient, and expand experimental techniques of brain function research.…”
Section: Discussionmentioning
confidence: 99%
“…This preliminary study indicated that curved lead implantation is relatively safe with an appropriately designed curved lead pathway. As the research on brain function moves forward, more and more researchers2627313233 worked on stimulating or recording multiple intracranial targets. The “curved lead pathway” method might contribute to the further development of electrophysiological techniques.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations